Clonal dominant grass Leymus chinensis benefits more from physiological integration in sexual reproduction than its main companions in a meadow - Guo, Jian; Li, Haiyan; Yang, Yunfei; Yang, Xuechen (Frontiers in Plant Science, 2023)
The bioecological characteristics of plants determine their status and role in the community. The advantages of dominant species in the community compared with companion species in terms of physiological and ecological characteristics remain unclear. When both dominant and companion species in grassland plant communities are clonal, these plants are able to share resources within clones (physiological integration). However, it is unclear how the clonal dominant and companion species differ in the effect of their physiological integration on sexual reproduction. We chose Leymus chinensis, the dominant species of the most widespread meadow plant communities in the semiarid and arid regions of northern China, and its main companion species L. secalinus, Calamagrostis ripidula, C. pseudophragmites, and C. epigeios and conducted a series of in situ field experiments in a homogeneous environment, including the determination of the phenotypic characteristics of reproductive ramets with connected (allowing physiological integration) and disconnected (preventing integration) tillering nodes for each species, as well as 15N leaf labeling of ramet pairs at the milk-ripe stage. In the clonal populations of the five grasses, physiological integration between vegetative ramets and reproductive ramets interconnected by tillering nodes significantly increased the leaf, stem, inflorescence and ramet biomasses of reproductive ramets, and relative changes in ramet biomass were greatest in L. chinensis. 15N labeling showed that vegetative ramets supplied nutrients to reproductive ramets through tillering nodes; the amount of translocated 15N per unit of reproductive ramet biomass was highest in L. chinensis. Overall, our results indicate that in the five clonal grasses, physiological integration between functionally different ramets under tillering node connections had a significant positive effect on sexual reproduction, indicating interspecific consistency in the contribution of physiological integration to sexual reproduction between the dominant and companion species, but this positive effect was greater in the dominant species L. chinensis than in the four main companion species. Therefore, differences in the physiological integration ability between the dominant and main companion species, identified for the first time in this study, may explain, at least partly, the dominance of L. chinensis in the community.